Optimalisasi Efisiensi Turbin Arus Laut Horizontal untuk Mendukung Kebutuhan Energi di Kawasan Pesisir Larantuka - Nikmah, Indana Zulfatun; Ayub, Fakhri Akbar (Fakultas Teknik UPN Veteran Jakarta, 2025)
This study aims to evaluate the energy conversion efficiency of Horizontal Axis Tidal Turbines (HATT) by varying blade length and angle of attack (AoA), and to assess their potential application in the coastal region of the Larantuka Strait. Numerical simulations were performed using Computational Fluid Dynamics (CFD) across nine turbine configurations to determine torque and power coefficient (Cp). The turbine with a 1 m blade and 10° AoA achieved the highest Cp value of 0.68. Meanwhile, the turbine with a 2 m blade and the same AoA, despite having a slightly lower Cp (0.66), produced the highest annual energy output of 737,619.7 kWh. With a net power output of 140.65 kW, approximately four units of this turbine are required to supply around 10% of Larantuka’s annual electricity demand. The selection of the optimal turbine model is based on a multi-objective approach that balances efficiency and energy output. These findings highlight the strong potential of tidal turbines as a renewable energy solution in eastern Indonesian coastal areas.